Self-supervised deep learning for missing image predictions - Yeoh, Shun Bin (Nanyang Technological University, 2023)
Deep learning has revolutionised the field of computer vision, enabling impressive advances in image classification, object detection, and segmentation. However, the success of supervised deep learning in computer vision is largely dependent on the availability of large annotated datasets, which can be time- consuming and expensive to acquire. Hence, self-supervised deep learning can be automated even with enormous volumes of unlabelled data, which reduces data labelling costs.